Islamization of human knowledge in theory and practice: achievements, challenges and prospects in the IIUM context - Hashim, Rosnani; Ssekamanya, Siraje Abdallah (IIUM Press, 2013)
The International Islamic University Malaysia (IIUM) aims to become a leading international centre of educational excellence which seeks to restore the dynamic and progressive role of the Muslim Ummah in all branches of knowledge and intellectual discourse.Its mission has been crystallized during the period of Professor Mohd Kamal Hassan, its third Rector, as Islamization, Integration, Internationalization and Comprehensive Excellence or commonly known as Triple ICE. This paper deals with the achievements, challenges and prospects in the IIUM context of one of these four missions, namely, Islamization.